iTRAQ analysis of urinary proteins: Potential use of gelsolin and osteopontin to distinguish benign thyroid goiter from papillary thyroid carcinoma - Jayapalan, Jaime Jacqueline; Lee, Cheng Siang; Lee, Ching Chin; Ng, Khoon Leong; Junit, Sarni Mat; Hashim, Onn Haji (Elsevier, 2018)
Background: Benign thyroid goiter (BTG) and papillary thyroid carcinoma (PTC) are often interchangeably misdiagnosed. Methods: Pooled urine samples of patients with BTG (n = 10), patients with PTC (n = 9) and healthy controls (n = 10) were subjected to iTRAQ analysis and immunoblotting. Results: The ITRAQ analysis of the urine samples detected 646 proteins, 18 of which showed significant altered levels (p < 0.01; fold-change > 1.5) between patients and controls. Whilst four urinary proteins were commonly altered in both BTG and PTC patients, 14 were unique to either BTG or PTC. Amongst these, four proteins were further chosen for validation using immunoblotting, and the enhanced levels of osteopontin in BTG patients and increased levels of a truncated gelsolin fragment in PTC patients, relative to controls, appeared to corroborate the findings of the iTRAQ analysis. Conclusion: The data of the present study is suggestive of the potential application of urinary osteopontin and gelsolin to discriminate patients with BTG from those with PTC non-invasively. However, this needs to be further validated in studies of individual urine samples.